Clinical case study on custom 3D printed collars for dropped head syndrome patients - Abir Dutta; Jim Ashworth-Beaumont; Sanganagouda Patil; Kia Rezajooi; Deepak M Kalaskar (3D Printing in Medicine)
Abstract Background Dropped Head Syndrome (DHS) is a neurological condition characterized by severe head and neck muscle atrophy, leading to difficulties in maintaining a straight gaze and experiencing severe neck pain during daily activities. Standard off-the-shelf cervical orthotic devices (Neck Collars) often fail to provide adequate support for patients with DHS. This feasibility study aimed to develop and implement a novel feedback-incorporated workflow for creating personalized 3D printed (Powder Bed Fusion) cervical orthotic devices for six DHS patients with varying pathologies. Case presentation A tailored workflow was devised and executed to produce bespoke 3D printed cervical orthotic devices for 6 DHS patients. The effectiveness of the collars in supporting patients during activities and reducing neck pain was assessed quantitatively and qualitatively using validated patient support questionnaires, Neck Disability Index, Visual Analog Score for Neck Pain, Global Cervical Angles (GCA), and Vertical Chin Brow Angles (VCBA) before and after intervention. Various clinical and design parameters were analysed to evaluate the collars’ efficacy in supporting patients and reducing neck pain. Patients exhibited an increase in GCA and a decrease in VCBA when using the collars as compared to their previous condition without those. The Visual Analog Score for Neck Pain decreased over the 6-month follow-up period, indicating positive implementation of the bespoke collars. Conclusion The personalized design and functionality of the 3D printed collars significantly improved patients’ quality of life, representing a significant advancement in rehabilitative and supportive healthcare interventions. This pilot study lays the groundwork for further large-scale cohort studies.